Radical intimacy : cultivate the deeply connected relationships you desire and deserve - Kors, Zoë (Hachette Go, an imprint of Hachette Books, 2022)
"Part practical guide, part client stories, part personal narrative, Zoë​ Kors draws on her experience as a sex and intimacy coach, thought leader, and relationship writer in sharing her powerful and practical methodology for nurturing and sustaining our intimate relationships over time. Kors guides the reader on a five-part journey through nine areas of opportunity for deepening intimacy with themselves, their partner, and their world, inviting them to embrace emotional, physical, and energetic self-mastery, which is required to skillfully relate with others. At the conclusion of each part, there are a collection of experiential exercises which support the reader in embodying the concepts they've just read"--